Evaluasi Workshop Penyusunan Proposal Penelitian Tindakan Kelas (PTK) Di Kota Padang Panjang - Donny Fernandez; R Candra; Martias Martias; Ahmad Arif (Universitas Negeri Padang, 2019)
Many can be used to improve the quality of teachers, among others, the implementation of Classroom Action Research (PTK). Quality of education will increase if teachers have an compose a pediagogic, personality, competence, and professional competency. PTK is the most appropriate step to improve the quality of learning. This quality improvement will positively affect teachers and student. For teachers, PTK is a reflective action over the learning that it does. All this time, the teacher is still considered and assumes his or her other resources out of less effort to improve the model and the learning model used. By performing the PTK, the teacher will know the actual condition that he or she faces. The workshop participants were provided with knowledge about the aspects of PTK also in the preparation of a good PTK and hope that they could provide refreshment to teachers relating to the PTK, so that the teachers could do the research as well as to solve the problem of the teaching process they lead. In addition, the objective is also to stimulate teachers to produce a written article published in the field of education. In the case of the service to the community this teacher is directly guided so as to be able to make the PTK in a separate, multi-disciplinary. From the activities undertaken by the team found a very significant improvement in terms of understanding of teachers in preparing the PTK. This is obtained from the pre test (question and answer) conducted ahead of the activity and post test post activities. Although there is a significant increase in understanding, there is still a need for teachers' independence and intuition in understanding the compilation of PTK more deeply. The community service team provides wide access for workshop participants to communicate both orally and through social networking so that the competence can be developed. In addition, the team devotion to the community also provides modules and literature that can be used as a reference in the preparation of PTK. This experimental research used survey method by distributing questionnaires to respondents with different subject expertise.The results showed that the use of ICTs in learning process has not been implemented optimally. This is caused by the low competence of teachers in the sector of information and communication technology. In addition, the lack of ICT infrastructure in schools causes a deceleration in the development of ICT-based learning models. Comprehensive improvement need to be implemented so that the development of ICT-based learnings model can be performed. The results of this study are expected to provide positive feedback to improve the quality of Indonesian education.